2013
DOI: 10.2134/agronj2013.0154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen and Planting Seed Size on Cotton Growth, Development, and Yield

Abstract: A standardized experiment was conducted during 2009 and 2010 at 20 location‐years across U.S. cotton (Gossypium hirsutum L.)‐producing states to compare the N use requirement of contemporary cotton cultivars based on their planting seed size. Treatments consisted of three cotton varieties with planting seed of different numbers of seed per kg and N rates of 0, 45, 90, and 134 kg ha–1. Soil at each trial location was sampled and tested for nitrate presence. High levels of soil nitrate (>91 N‐NO3– kg ha–1) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 31 publications
9
41
0
Order By: Relevance
“…13 by showing the nutrient use efficiencies for nitrogen, phosphate, and potash by region (mass of cotton fiber produced per mass of nutrient applied). The consistent value near 10 kg of fiber per kg of nitrogen across all regions is encouraging, as that is very close to the current extension recommendations for cotton, which were recently verified by Main et al (2013). As nitrogen is removed from the field in the cottonseed, it has to be consistently replaced.…”
Section: Soil Managementsupporting
confidence: 82%
See 1 more Smart Citation
“…13 by showing the nutrient use efficiencies for nitrogen, phosphate, and potash by region (mass of cotton fiber produced per mass of nutrient applied). The consistent value near 10 kg of fiber per kg of nitrogen across all regions is encouraging, as that is very close to the current extension recommendations for cotton, which were recently verified by Main et al (2013). As nitrogen is removed from the field in the cottonseed, it has to be consistently replaced.…”
Section: Soil Managementsupporting
confidence: 82%
“…Data for GHG distribution are not shown, as they were closely correlated to energy, with the exception of nitrogen, which becomes even more dominant due to assumed in-field nitrous oxide emissions (Synder et al 2012). Since the 2008 survey, Cotton Incorporated has extensively researched nitrogen management recommendations for modern cotton varieties (Main et al 2013). The 2015 survey data show that producers are achieving nitrogen use efficiencies very close to…”
Section: Energy Use and Greenhouse Gas (Ghg) Emissions Energy Hotspotmentioning
confidence: 99%
“…None of the fiber quality attributes was influenced by the N treatments (Table 5). Similarly, Main et al (2013) [15] reported only 11 of 20 site-years across the Cotton Belt region in which there was a cotton lint yield response to applied N. They observed when 45 kg·N·ha -1 was applied, yields were greater than when no N was applied, but were less than yields where 90 to 134 kg·N·ha -1 was applied on the N responsive site-years; however, when all the site-years, both N responsive and non-responsive, were considered, 45 kg·N·ha -1 increased yields above no applied N, but additional N above 45 kg·N·ha -1 did not improve lint yield.…”
Section: Effects Of In-season Side-dress N Applications On Plant Heightmentioning
confidence: 98%
“…The higher nitrogen demand later in the growth cycle of the plant makes in‐season applications of nitrogen critical to the rapid growth and fruiting development occurring in a short time period. Nitrogen fertilizer rate and plant development need to be balanced since overfertilizing with nitrogen leads to increased vegetative growth and reduced production of fruiting sites, resulting in lower yields (Lemon et al, 2009; Main et al, 2013). Research across 20 cotton‐growing sites reported that nitrogen application rate affected plant height and number of nodes (Main et al, 2013).…”
mentioning
confidence: 99%
“…Nitrogen fertilizer rate and plant development need to be balanced since overfertilizing with nitrogen leads to increased vegetative growth and reduced production of fruiting sites, resulting in lower yields (Lemon et al, 2009; Main et al, 2013). Research across 20 cotton‐growing sites reported that nitrogen application rate affected plant height and number of nodes (Main et al, 2013). Specifically, increased nitrogen rates resulted in more plant height and more nodes but also resulted in delayed crop maturity (Main et al, 2013).…”
mentioning
confidence: 99%